Analysis of factors affecting algae removal from petrochemical industry wastewater using salts as biocide - N., Zainol; Nur Syahida, Hasbullah (IOP Publishing, 2020)
Biocide was used in this study to remove algae in petrochemical wastewater. By using biocide, it has the advantage of producing a high quality effluent for reasonable operating and maintenance costs. Four independent factors, such as type of biocide, ratio of biocide mass to synthetic wastewater volume (B/W), agitation, and hydraulic retention time (HRT) were investigated. A two-level factorial design was used to investigate the effect of the independent factors as well as the interaction factors on the pH and reduction of algae mass (%). Some of the independent factors were shown to have a significant effect on both pH and reduction of algae mass (%). For pH, the order of significance was HRT > agitation > type of biocide > B/W ratio. It showed that the interaction factor of agitation *HRT had the strongest effect (5.85%) on the pH value. For the reduction of algae mass (%), the order of significance was HRT > B/W ratio > agitation > type of biocide. It showed that interaction factor of agitation*HRT had the strongest effect (8.79%) on the reduction of algae mass (%). From the analysis, the selected best conditions by Design Expert were determined at table salt as biocide, 3:2 B/W ratios, 100 rpm agitation rate, and HRT at 15 hours. It can be concluded that HRT was strongly influencing the application of salt in algae removal from petrochemical industry wastewater and the process could remove up to 85% of algae.